Effects of Ultra‐High Pressure Tenderizing Treatment on the Quality Characteristics of Venison. Issue 2 (24th March 2015) - Zhou, Yajun; He, Qin; Su, Dan; Huang, Hui
Abstract: To improve quality of venison, the quality characteristics affected by the ultra‐high pressure tenderizing method were examined. Different pressures and pressurizing times were studied to compare their different effects on myofibrillar fragmentation index (MFI), content of soluble protein (CSP), collagen heat solubility and texture properties, which could present tenderizing effects. The results showed that ultra‐high pressure treatment can tenderize venison and had significant effects on the proteins therein. The optimized parameters were: a pressure of 300–400 MPa and a pressurizing time of 2–6 min. Compared with a control, MFI of treated samples increased by 32%, collagen heat solubility increased, CSP decreased slightly, hardness decreased by about 58.7% and chewiness decreased by 75%. Ultra‐high pressure treatment, as an emerging technology, exerted a significant influence on improving the quality characteristics of venison. Practical Applications: Venison is suitable for human consumption. The number of venison consumers has gradually increased because of its advantages of high protein content, low cholesterol and ease of digestion. Most deer are raised for long enough to allow their antlers to be taken and the quality of the resulting venison is poor. It is essential to improve the quality of venison to be sold in the market. This study of ultra‐high pressure methods used to tenderize venison is important to the development of the venison market. Consumers are more likely to purchase venison if it is tender. The results of this study are helpful to the further study of ultra‐high pressure methods of improving the quality of venison and, as such, are of practical significance.